Multicolored luminescent CdS nanocrystals - 张军 狄晓威 刘志亮 徐刚 徐盛明 周兴平 (Transactions of Nonferrous Metals Society of China, 2007)
The observation of efficient blue, green, orange and red luminescence from CdS nanocrystals made by using a reverse micelle method was reported. The blue luminescence about 480 nm is attributed to the radiative recombination of electron-hole pairs. The red luminescence around 650 nm is due to the radiative recombination of the exciton trapped in the nanocrystal surface defect states. The combination of different portion of band-edge emission and surface trap state emission results in green and orange luminescence for the nanocrystals. The CdS nanocrystals with efficient multicolored luminescence may find potential application in full color displays and biolabelings.